The mosque of Granada Mezquita de Granada (Cairo : Safeer International Publishing, 2002)
The Mosque of Granada which took 21 years to complete. A 45 minute documentary of the most important event in the Islamic calendar of Europe.
Editor, Mohd Zaafir James
Narrator: Jason Daud Cottam
Keywords: Muslim -- Europe; Islam -- Europe